The Challenges of Using Online Game Accounts as Collateral in Indonesian Civil Law (A Case Study of an Instagram-based Game Account Pawn Service) - Taslim, Mahardika; Mandasari, Annisa (Moccasin Journal De Public Perspective, 2025)
The modern application of games is not limited to entertainment but it is also used in sphere of sports and business. Another feature that can be distinguished in the business world is the existence of game accounts that have great monetary value. The economic value of such accounts is due to their quality, demand, and rarity of in-game items. In the past, game accounts were limited to purchase-sale transactions but in the recent times business entities are using such accounts as a security thus necessitating a critical analysis of game accounts in terms of property law and applicable security law to online game accounts. This research will use a normative legal research approach, where the legal approach will be a statutory research approach, which relies on the provisions of the law and other scholarly articles as legal sources. The results show that the owner of a game account online is technically a possessor but not an owner because property rights are inseparable characteristics of ownership. As a result, the game developer or publisher solely owns the game with the player only getting a license. It is a must to be aware of the statutory limitations as the nature of account transfer agreements is not legal when they do not meet the fourth condition of Article 1320 of the Indonesian Civil Code; thus, the agreement is considered invalid. The scheme of pawn proposed by the service of the @Pawn cannot be considered valid as well, and it is not in accordance with the principles of the Security Law.